ANALISIS TINGKAT KECUKUPAN ENERGI SISWA YANG MENGIKUTI EKSTRAKURIKULER PENCAK SILAT DI SMK NEGERI 1 KEMLAGI MOJOKERTO - HASYIM, ZUSRON (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract One of the optimal performance achievement on pencak silat beside require regular training, student who following pencak silat extracurricular also need good nutrient. Appropriate nutrient is main basic for prime performance for athlete during match. Student who student who following pencak silat PSHT extracurricular on SMKN 1 Kemlagi Mojokerto still need knowledge and information concerning the energy sufficiency on each student. The purpose of this research was to found out the description of energy sufficiency, carbohydrate, fat, protein on student who following pencak silat extracurricular. Research design applying descriptive research with quantitative approach. Data collecting by survey method technique with the amount of sample of 30 respondents namely student who following pencak silat extracurricular. Data collecting apply food recall method. Analysis data by SPSS 16.0 to obtain frequency, standard deviation and mean. Research result found that the mean of student’s energy sufficiency are 1201.16 kkal and its standard deviation are 335.08. On male students the mean of energy sufficiency is 1314.28 kkal and its standard deviation is 415.60. While on female students the mean of protein sufficiency is 45.16.gram and its standard deviation is 13.04. On male students the mean of protein sufficiency is 46.27.gram and its standard deviation is 12.32. On Female students the mean of fat sufficiency is 33.11.gram and its standard deviation is 13.05. While on male students the mean of protein sufficiency is 31.64.gram and its standard deviation is 11.59. The mean of carbohydrate sufficiency on female student is 155.11 gram and its standard deviation is 37.81. While on male students the mean of carbohydrate sufficiency is 167.45 gram and its standard deviation is 41.98. The research results above show that most of student’s energy sufficiency belong to enough category. The implication of this research is energy sufficiency required by students to reach optimal achievement. So that, instructor, parent, and student pay attention to nutrients on its food. Keywords: Energy sufficiency analysis, Pencak Silat